State of the art applications of biotechnology in wastewater treatment. - Jose, Wilfredo I. (Philippine Engineering Journal)
Biological waste treatment processes such as the activated sludge and biomethanation use naturally occurring microorganisms. With environmental biotechnology, the performance of these processes can be improved. Special strains can be isolated to treat xenobiotics and other poorly degradable substances found in municipal sewage and industrial wastes.